A Rare Case of Migration of Hyaluronic Acid Gluteal Injection to the Medial Thigh Presenting as a Soft Lump - Saad, Ahmed; Iyengar, Karthikeyan P.; Davies, A. Mark; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2023)
Introduction Hyaluronic acid (HA) is a widely accepted agent most commonly used as a dermal filler in facial aesthetic/cosmetic medicine. More recently, HA has been utilized for gluteal augmentation. The common side effects of HA injection are often minor and self-limiting. HA migration is a very rare complication.Case Report We describe a rare case of HA buttock injection migration in a transgender patient, appearing as a superficial lump on right thigh representing a diagnostic dilemma. We highlight the need of a clinical suspicion and discuss the appropriate investigations for guided management of such patients.Conclusion It is essential for reporting radiologist to be aware of the commonly used injectable fillers, their complications, and imaging findings to avoid misdiagnosis and guide optimal patient management.
Keywords: Hyaluronic acid; gluteal augmentation; filler injections; magnetic resonance imaging